Preliminary results for the breeding bird atlas of Bucharest (Romania): Data from 2016–2023 - Florinel-Dănuț Drăgan; Dumitru Murariu; Roxana-Ștefania Drăgan (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”)
Urban bird atlases offer solid information about the distribution and breeding status of birds and can help in urban planning, education, research, pest control, and many other fields of work. In Romania, the first urban atlas was completed for Cluj city in 2017. Our study offers solid information about breeding birds from the capital city, Bucharest, the biggest city in Romania. Fieldwork was conducted with the help of volunteers in the period of April–June, from 5:00 to 10:00 AM, starting in 2016 and lasting until 2023. Data was collected from squares of 1x1 km, summing a total of 159 complete squares from the 251 covering the whole city, with over 70.000 bird observations. Mobile apps were used for data collection and orientation inside the monitoring squares. Before the atlas study started, few bird observations were recorded; since 2016, thousands of observations have been made, with new species being discovered every year. Occasional observations and data from artificial nests were accepted too. Because of the small number of recorders, we divided the squares into two classes of importance: the main area, which includes the squares inside a buffer zone of 6 km from the city center, and a secondary area for the rest of the squares, focusing our efforts to finish the squares in the main area. More volunteers are needed, and also new approaches to collecting data on nocturnal and invasive species.